Distinct renin/aldosterone activity profiles correlate with renal function, natriuretic response, decongestive ability and prognosis in acute heart failure. (15th December 2021) - Biegus, Jan; Nawrocka-Millward, Sylwia; Zymliński, Robert; Fudim, Marat; Testani, Jeffrey; Marciniak, Dominik; Rosiek-Biegus, Marta; Ponikowska, Barbara; Guzik, Mateusz; Garus, Mateusz; Ponikowski, Piotr
Abstract: Background: Although renin-angiotensin-aldosterone system (RAAS) activation is believed to be the major driver of acute heart failure (AHF) episodes our understanding of its prevalence and clinical relevance in contemporary settings is incomplete. Methods: Serum renin and aldosterone were measured at day-1 and at discharge in patients ( n = 211) that were hospitalized between 2016 and 2017 for AHF in a single cardiology center. The population was profiled based on upper limits of normal (ULN) of both biomarkers assessed at day-1 and linked with the clinical course and outcomes. Results: The study population constituted of three profiles: RAAS−/− ( n = 121 [57%]); RAAS+/− ( n = 60 [28%]); and RAAS+/+ ( n = 30 [14%]). The RAAS+/+ profile had the lowest blood pressure and serum sodium at admission, day-2 and discharge compared to the other profiles ( p < 0.001). The RAAS+/+ patients had significantly lower urine Na+ at admission (57.8 ± 36.7 vs 97.3 ± 31.3 and 86.4 ± 35.0), day-1 (52.7 ± 32.7 vs 85.3 ± 36.3 and 75.5 ± 33.9) mmol/l, vs RAAS−/− and RAAS+/− profiles, respectively, all p < 0.001. There was also a gradual decrease of renal function across increasing RAAS profiles. The RAAS+/+ profile received higher dose of furosemide at discharge 120 [80–160] vs the other profiles 80 [40–120] mg, p < 0.01. The risks of one year mortality or HF rehospitalization increased across the RAAS profiles ( p < 0.001). The trajectory of renin or aldosterone change during hospitalization was not related to outcomes. Conclusions: The RAAS overactivity is not essential for development of AHF. However, elevated RAAS is a marker of more advanced stages of heart failure, is related to low natriuresis and adverse clinical outcomes. Graphical abstract: Unlabelled Image Highlights: In contemporary population, the RAAS overactivity is not essential for development of clinical picture of acute heart failure There appear to be differential phenotypes of water/sodium handling disabilities among patients hospitalized for AHF RAAS overactivity is related with low natriuresis, high diuretic demand and poor outcome in AHF. The trajectory of renin during hospitalization as a result of reduction of extracellular volume did not impact the prognosis.